Socio-economic impacts of land degradation at Gunungsari Village of Tlogowungu District, Pati Regency, Central Java - C Y Lastiantoro (Brawijaya University, 2015)
The purpose of this study was to evaluate the socio-economic impact of land degradation and the role of watershed management in the development of agroforestry to support food safety and security. This study used descriptive analytical method that was based on the observations, interviews, and literature survey. Thirty respondents were randomly selected for this study. The results showed that the socio-economic impact of land degradation was the decline production of cassava for the last four years. Watershed management played an important role in the development of agroforestry to support food security. Agroforestry-based soil conservation did not run optimally due to a number of obstacles in its development. The development constraints were large area of critical lands and lack of technology transfer on watershed management. Policies needed in the development of agroforestry-based soil conservation to support of food safety and security are improvement of formal and non–formal educations, adoption of watershed management technology, and empowerment of farmers for agroforestry development.